Karyotype analysis of Capsicum pubescens R & P (Solanaceae) "rocoto" - Guevara, Misael (2000)
Karyotype analysis of Capsicum pubescens (Solanaceae). Chromosomes are described, compared and illustrated, using a modified orcein staining technique. C. pubescens has a diploid number of 2n = 24 chromosomes, 11 pairs are metacentric and one pair is submetacentric.